(untitled) (Contemporary Journal of Social Science Review, 2025)
This article intends to explore the postmodern concept of hypertextuality in Barbara Kingsolver’s Demon Copperhead (2022) by applying Gérard Genette’s notion of hypertextuality. This research aims to show that there is no originality in literature and any literary work can be the repetition, continuation, inspiration or mixture of previous texts. In this way, the study shows how a twenty first Century’s literary work like Demon Copperhead (2022) can be the hypertext of Dickens’s nineteenth-century well-known novel David Copperfield (1850). Moreover, such postmodern research widens various ways of concentration on the literary works, so that, one could interpret in what ways two texts are united and grafted which results in either parody or pastiche. This study attempts to demonstrate mostly those focused aspects in both the texts that highlight the concept of hypertextuality. Furthermore, this paper includes the analyses of both protagonists i.e. Demon and David and narration of the both novels from the perspective of main characters. The research is significant for researchers and academia to gain insight into the unique postmodern aspect of hypertextuality.